KUALITAS LABA SEBAGAI PEMODERASI HUBUNGAN ANTARA TATA KELOLA DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM - ANNISA KANTI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study was to examine the effect of Corporate Governance, and financial performance on stock returns with earnings quality with Accruals Quality proxy consisting of Innate Accruals Quality and Discretionary Accruals as moderating variable. This study uses multiple regression testing because the data used in the dependent variable and independent variables use the ratio scale. The research sample is a manufacturing company listed on the Jakarta Stock Exchange by taking a sample of 49 companies from 2016. Determination of the sample was done using purposive sampling method. Based on the results of the analysis, it can be concluded that CG and financial performance (Profitability) affect stock returns, while other financial performance (Leverage and Dividend Policy) also Earnings Quality (Accruals Quality) do not affect stock returns. Accruals Quality can moderate CG and Innate Accruals Quality can moderate the variables CG and PROF on stock returns.